"Is the Ground Ready?" Exploring the Use of Feminist Pedagogy in Refugee Education in Greece Through a Feminist, Intersectional Approach - Mytakou, Tereza (Trinity College Dublin. School of Linguistic Speech & Comm Sci. C.L.C.S., 2024)
The present study explores the use of a feminist pedagogy approach in a refugee education context in Greece. Its main aim is to discuss whether the ground is ready for such an approach, through examining the following three sub-questions: "What are the obstacles of implementing feminist pedagogy in a refugee education setting in Greece?" "What are the opportunities?" "How do teachers and students perceive of this approach?". The study assumes a feminist and intersectional epistemological and methodological framework, which allows for greater teacher and researcher reflexivity and awareness of positionality. Data collection was conducted in a school for refugee children on the Greek border-island of Leros, where the author worked as a teacher of English for eight months. The following tools of data collection were used: i) semi-structured interviews with eight educators and two managers, ii) classroom discussions with two teenage students, iii) the keeping of a researcher diary. The data was analysed using Braun and Clarke's (2021) reflexive thematic analysis framework, and produced the three themes of "Gender as a difficult and complex construct", "Trauma as present, but not defining" and "Culture/language as barriers". The thesis considers both the obstacles to implementing a feminist pedagogy approach, as well as the opportunities which arose throughout the research. The findings point to the immense value of employing feminist pedagogy in refugee education, mainly due to its aims of developing critical consciousness around issues of gender and oppression, and its potential to assist in dealing with trauma and fostering resilience, both of which are interlinked with the aims of refugee education.
APPROVED
Keywords: refugee education; reflexivity; feminist research methodology; feminist pedagogy; reflexive thematic analysis